2021
DOI: 10.1186/s13048-021-00913-x
|View full text |Cite
|
Sign up to set email alerts
|

CXCL14 facilitates the growth and metastasis of ovarian carcinoma cells via activation of the Wnt/β-catenin signaling pathway

Abstract: Background There is an urgent need to identify potential targets in anticancer therapy to improve the survival and prognosis of patients with ovarian cancer (OC). Herein, we investigated the functional significance of chemokine (C-X-C motif) ligand 14 (CXCL14) in OC cell growth and epithelial–mesenchymal transition (EMT). Methods qRT PCR and western blotting was used to detect CXCL14 mRNA level and protein expression, respectively. The functional m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Thus it was suggested to be a potential direction to improve OC-related immunotherapy [ 55 , 56 ]. Moreover, researchers also found that the upregulation of CXCL14 facilitated OC-related tumor cell proliferation through STAT3 signaling pathway, while promoted epithelial-mesenchymal transition and tumor metastasis through Wnt/β-catenin pathway [ 57 , 58 ]. All of these researches elucidated the significance of CXCLs for OC, supporting the relevant exploration of therapeutic value of CXC chemokines acting as biomarkers or targets.…”
Section: Cxcl Family and Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus it was suggested to be a potential direction to improve OC-related immunotherapy [ 55 , 56 ]. Moreover, researchers also found that the upregulation of CXCL14 facilitated OC-related tumor cell proliferation through STAT3 signaling pathway, while promoted epithelial-mesenchymal transition and tumor metastasis through Wnt/β-catenin pathway [ 57 , 58 ]. All of these researches elucidated the significance of CXCLs for OC, supporting the relevant exploration of therapeutic value of CXC chemokines acting as biomarkers or targets.…”
Section: Cxcl Family and Diseasesmentioning
confidence: 99%
“…1 The roles of CXCL family in cancers. Majority of CXCL chemokines binding to corresponding receptors are involved in tumor growth via the activation of different signaling pathways (STAT3 [29,105], NF-κB [31], Ras [7], MAPK [131], PI3K [47], TGF-β [7], β-catenin [57], ERK1/2 [47]). It eventually affects proliferation, invasion, migration and transformation of cancer cells, immune control, and tumor angiogenesis [24,47,48,58,63,69].…”
Section: Cxcr8mentioning
confidence: 99%
“…Furthermore, addition of recombinant mouse CXCL14 protein to BMDMs or RAW264.7 cells stimulated ERK phosphorylation (Supplementary Fig, 10). In ovarian cancer, CXCL14 was reported to activate b-catenin (40), however, we could not detect an increase in nuclear b-catenin by treating BMDMs with recombinant CXCL14 (Supplementary Fig, 10). Whether CXCL14-mediated polarization and recruitment of M2-like macrophages are through ERK1/2-pathway requires further investigation.…”
Section: Discussionmentioning
confidence: 73%
“…CXCL14 was also shown to function as a chemokine for M2-polarization of macrophages (19). Interestingly, Gao et al (40) reported that CXCL14 facilitated ovarian cancer cell invasiveness through activation of Wnt/ β-catenin signaling pathway, although the mechanism is unknown. We found that knockdown of CXCL14 in EC-OSB cells reduced the EC-OSB-mediated upregulation of M2-macrophage genes ( Arg1, Clec10a, IL10, Mrc1 ) in BMDMs ( Fig.…”
Section: Resultsmentioning
confidence: 99%